Spermine delivered by ZIF90 nanoparticles alleviates atherosclerosis by targeted inhibition of macrophage ferroptosis in plaque - Yuwu Chen; Biyi Xu; Quan Lin; Xinxin Zhu; Ying Lv; Xiaoxuan Bai; Xiuzhu Weng; Jie Du; Man Li; Yuxiao Zhu; Junke Mou; Mengyang Wang; et al. (Journal of Nanobiotechnology)
Abstract Background Nowadays, emerging evidence have suggested that the ferroptosis of macrophages could contribute to the progression of atherosclerosis (AS). Meanwhile, Spermine (Sp) could serve as an endogenous small molecule exhibiting a wide range of cardiovascular protective effects. Methods Zeolitic imidazolate framework-90 (ZIF90) nanoparticles were synthesized and utilized to create a novel delivery nanosystem encapsulated with Sp (CD16/32-ZIF90@Sp). The efficacy of CD16/32-ZIF90@Sp in protecting against AS and ferroptosis was evaluated in ApoE−/− mice and macrophages, with a focus on assessing potential adverse effects in vivo. Results CD16/32-ZIF90@Sp exhibited reliable and stable delivery of Sp within acidic environments and ATP sensitivity. CD16/32-ZIF90@Sp effectively reduced the cytotoxicity of Sp. As is evidenced by in vitro and vivo experiments, CD16/32-ZIF90@Sp showed precise targeting of macrophages within atherosclerotic plaques and ox-LDL-activated macrophages. Furthermore, treatment with CD16/32-ZIF90@Sp effectively attenuated the progression of AS and the ferroptosis of macrophage within plaque in ApoE−/− mice without causing significant side effects. Mechanistically, we found that CD16/32-ZIF90@Sp inhibited ferroptosis via improving mitochondrial function and upregulating the expression level of GPX4/xCT. Conclusion Our study demonstrated that CD16/32-modified ZIF90 nanoparticles could effectively target macrophages within atherosclerotic plaques, leading to the inhibition of atherosclerotic plaque progression in ApoE−/− mice. These effects were attributed to the enhancement of mitochondrial function and the inhibition of macrophage ferroptosis, with limited side effects. Graphical Abstract